Analisis Perilaku Konsumen dalam Pembelian Produk yang sudah Memiliki Izin Usaha, Studi Kasus Produk Abon Ikan Pedo Kota Lubuk Linggau - Metha Aditya Putri; Endar Pradesa (IPM2KPE, 2025)
This study aims to analyze consumer behavior toward pedo fish floss products that have a legal business license in Lubuklinggau City. The research method used is a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. The results indicate that business legality has a positive impact on consumer trust, increasing sales, and expanding the market through digital marketing strategies and participation in various exhibitions. The conclusion of this study is that internal factors such as perception and motivation, as well as external factors such as business legality and marketing strategy, significantly influence consumer behavior in purchasing decisions for pedo fish floss products. Keywords: Consumer Behavior, Pedo Fish Floss, Business Legality, Marketing Strategy